(untitled) (Journal of Interdisciplinary Insights, 2024)
This paper explores the evolution and innovation of Chinese university dance programs within the context of global trends in dance education. It examines the historical context of dance education in China, highlighting the transition from traditional forms to the incorporation of contemporary and Western techniques. Recent reforms and structural changes initiated by the Chinese State Council’s Academic Degrees Committee are analyzed, including the separation of dance from "Music and Dance" and its implications for the discipline. The paper discusses the dual structure of dance discipline, which encompasses professional practice-oriented degrees and academic theory-based degrees, and explores mechanisms for integrating theory and practice in dance education. Technological advancements and their impact on dance practice and education, as well as the role of dance in contemporary Chinese society, are examined. Challenges and opportunities facing Chinese university dance programs are discussed, along with future prospects for the field.